2019
DOI: 10.3390/rs11111340
|View full text |Cite
|
Sign up to set email alerts
|

Dual and Single Polarized SAR Image Classification Using Compact Convolutional Neural Networks

Abstract: Accurate land use/land cover classification of synthetic aperture radar (SAR) images plays an important role in environmental, economic, and nature related research areas and applications. When fully polarimetric SAR data is not available, single-or dual-polarization SAR data can also be used whilst posing certain difficulties. For instance, traditional Machine Learning (ML) methods generally focus on finding more discriminative features to overcome the lack of information due to single-or dual-polarimetry. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…LCLU mapping has a long tradition in Earth observation, and with 13% of all publications, LCLU is the third largest group of applications of the reviewed papers. The majority of multi-class LCLU publications conducted proof-of-concept studies on a local scale by demonstrating how deep-learning models can be applied in complex scenarios with many classes by reaching high spatial accuracies [188][189][190][191][192][193][194][195][196]. However, large-scale applications were also investigated, which often classify more aggregated classes due to the lower spatial resolution of the input data [58,73,[197][198][199][200][201].…”
Section: General Land Cover and Land Usementioning
confidence: 99%
“…LCLU mapping has a long tradition in Earth observation, and with 13% of all publications, LCLU is the third largest group of applications of the reviewed papers. The majority of multi-class LCLU publications conducted proof-of-concept studies on a local scale by demonstrating how deep-learning models can be applied in complex scenarios with many classes by reaching high spatial accuracies [188][189][190][191][192][193][194][195][196]. However, large-scale applications were also investigated, which often classify more aggregated classes due to the lower spatial resolution of the input data [58,73,[197][198][199][200][201].…”
Section: General Land Cover and Land Usementioning
confidence: 99%
“…High quality classification mapping has been produced by applying either classical machine learning, such as random forest and the support vector machine, or complex deep learning methods on S1 time series. Recently, deep learning (DP) techniques [32,34,35] have shown that neural network models are well adapted tools to automatically produce land cover mapping from information coming from both optical [36] and radar [37] sensors. The main characteristic of these models is the ability to simultaneously extract features optimized for image classification.…”
Section: Introductionmentioning
confidence: 99%
“…Because of this, the discussed approaches developed and tested specifically for PolSAR imagery at a higher resolution cannot be considered applicable for a widearea mapping, yet. Similarly, Ahishali et al [64] applied endto-end approaches to SAR data. They have also worked with single polarized COSMO-SkyMed imagery.…”
Section: B Deep Learning In Remote Sensingmentioning
confidence: 99%